2017
DOI: 10.1371/journal.pone.0180972
|View full text |Cite
|
Sign up to set email alerts
|

Integrative functional analyses using rainbow trout selected for tolerance to plant diets reveal nutrigenomic signatures for soy utilization without the concurrence of enteritis

Abstract: Finding suitable alternative protein sources for diets of carnivorous fish species remains a major concern for sustainable aquaculture. Through genetic selection, we created a strain of rainbow trout that outperforms parental lines in utilizing an all-plant protein diet and does not develop enteritis in the distal intestine, as is typical with salmonids on long-term plant protein-based feeds. By incorporating this strain into functional analyses, we set out to determine which genes are critical to plant protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 76 publications
2
16
2
Order By: Relevance
“…In HG-50SBM + 2SPN fish, cyp27a1.2 , cyp27a1.4 , and cyp7a1 were downregulated, while cyp46a1.1 was upregulated, suggesting a metabolic redirection towards 24(S)-hydroxycholesterol, leading to suppression of Th17 differentiation. These results are consistent with those reported by Abernathy et al [ 81 ], where liver tissues from rainbow trout tolerant to a plant diet were subjected to functional analysis. These authors documented upregulated cytochrome P450A1 and T cell signaling, which suppressed interleukin-17 receptor E-like (IL17REL) expression.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In HG-50SBM + 2SPN fish, cyp27a1.2 , cyp27a1.4 , and cyp7a1 were downregulated, while cyp46a1.1 was upregulated, suggesting a metabolic redirection towards 24(S)-hydroxycholesterol, leading to suppression of Th17 differentiation. These results are consistent with those reported by Abernathy et al [ 81 ], where liver tissues from rainbow trout tolerant to a plant diet were subjected to functional analysis. These authors documented upregulated cytochrome P450A1 and T cell signaling, which suppressed interleukin-17 receptor E-like (IL17REL) expression.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, upregulation of il-17 is directly related to intestinal inflammation found in fish that cannot tolerate plant-based diets. These authors suggest that tolerant fish display different autoimmune or other detoxification responses to utilize plant proteins, avoiding the onset of enteritis [ 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fermentation of soybean meal prior to feeding has also been tested in turbot with encouraging results, suppressing the intestinal inflammation and enhancing the intestinal integrity [ 45 ]. Furthermore, efforts in selecting resistant fish with increased tolerance to plant diets have been made in some species such as rainbow trout ( Oncorhynchus mykiss ) [ 46 ]. In yellowtail kingfish, efforts in finding alternatives to soybean meal showed that poultry byproduct, faba bean and lupin kernel meals represent good protein sources compared to corn gluten and blood meals [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Effects of plant-based diets have been largely studied, but only few transcriptomic studies have analysed the effect of fish genetic background. Overall, these studies indicated only a limited number of genes to be differentially expressed according to the genotype in RBT [ 20 , 21 ], in salmon [ 11 ] or in sea bass [ 14 ]. In the present experiment, we found a high number of genes differentially expressed between genotypes, with a cut-off p-value corrected for multiple testing, controlling thus the number of false positives.…”
Section: Discussionmentioning
confidence: 99%
“…A study on European sea bass revealed differences between two families characterized by their different abilities to use a plant-based diet [ 14 ]. And only two studies focused on RBT, and analysed two families with different ability to grow with a diet devoid of fishmeal [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%